Prevalence of severe acute respiratory syndrome Coronavirus 2 antibodies among market and city bus depot workers in Lima, Peru - Tovar, Marco (2022)
We report severe acute respiratory syndrome coronavirus 2 antibody positivity among market and city bus depot workers in Lima, Peru. Among 1285 vendors from 8 markets, prevalence ranged from 27% to 73%. Among 488 workers from 3 city bus depots, prevalence ranged from 11% to 47%. Self-reported symptoms were infrequent.